Proceedings of the 2017 Conference on Designing Interactive Systems 2017
DOI: 10.1145/3064663.3064742
|View full text |Cite
|
Sign up to set email alerts
|

Calming Children When Drawing Blood Using Breath-based Biofeedback

Abstract: Blood sampling is a common and necessary procedure in the treatment and diagnosis of a variety of diseases. However, it often results in painful and stressful experiences for children. Designed together with domain experts, Pufferfish is a breath-controlled biofeedback game technology with bespoke airflow sensor that aims to calm children during blood sampling procedures. An initial randomized controlled trial was conducted in which 20 children aged 6-11 were assigned to one of two conditions involving either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
11
0
3
Order By: Relevance
“…Especially for youth it is important to keep them engaged and motivated and games are seen as an ideal way to achieve this [22][23][24][25]. Promising results of game-based biofeedback have been found for emotion regulation and the treatment of stress and anxiety in youth [20][21][26][27][28][29][30] with some games even being just as effective as a gold-standard treatment [31].…”
Section: Biofeedback Video Gamesmentioning
confidence: 99%
“…Especially for youth it is important to keep them engaged and motivated and games are seen as an ideal way to achieve this [22][23][24][25]. Promising results of game-based biofeedback have been found for emotion regulation and the treatment of stress and anxiety in youth [20][21][26][27][28][29][30] with some games even being just as effective as a gold-standard treatment [31].…”
Section: Biofeedback Video Gamesmentioning
confidence: 99%
“…Prior work with TUIs to guide children's breathing has shown that active calming techniques are more effective than passive ones [25]. Sonne initially designed the "ChillFish" to calm children with ADHD and later tested it as a means of calming children while they had blood drawn [23][24] [25].…”
Section: Biofeedback Devices and Tuis Formentioning
confidence: 99%
“…There are also commercial systems for respiratory muscle training for children with lung-related diseases [61,68]. Furthermore, various studies on breathing games target Positive Expiratory Pressure (PEP) physiotherapy for people with Cystic Fibrosis (CF) [41,67], relaxation exercises [1,43,51] 3 including an attempt of calming children during drawing blood [52], and investigating entertainment-purposes [24,35,54].…”
Section: Related Workmentioning
confidence: 99%
“…Building on the related work, a variety of applied practical principles, and the co-design sessions we made SpiroPlay. Similar to [52], SpiroPlay is a real-time responsive app created in Unity running on an Android tablet with a Bluetooth connection. We use Air Next (NuvoAir) a commercially available affordable turbinebased spirometer handheld device.…”
Section: Spiroplay App: a Suite Of Gamesmentioning
confidence: 99%